Prevalence of Malaria among Patients attending Federal Medical Centre, Owerri, Imo State, Nigeria - Mohammed, Aisha; Oda, Onoja (Sahel Journal of Life Sciences FUDMA, 2024)
The malaria parasite is a parasitic protozoan (a group of single-celled microorganisms) that inflicts humans with malaria. It is responsible for a significant proportion of the health burden of developing countries. Thus, this study aimed to evaluate the prevalence of malaria among patients attending the Federal Medical Centre Owerri, Imo State, Nigeria. A total of 150 patients consented to participate. Malaria diagnosis was performed using rapid diagnostic test kits and microscopic examination of Giemsa-stained blood film. Questionnaires were administered to gather socio-demographic data. The analysis revealed a 53% prevalence of malaria. Statistical analysis indicated associations between malaria occurrence and gender, educational level, and economic status. This study highlights the high prevalence of malaria among patients at FMC Owerri.